The Role of the Mobile Brigade in Social Conflict Management - Gunawan Arifin (Program Pascasarjana Universitas Muhammadiyah Palu, 2025)
This study aims to: (1) examine the role of the Mobile Brigade in addressing social conflicts between Rarampadende Village and Pesaku Village, West Dolo District, Sigi Regency; and (2) identify the obstacles faced by the Mobile Brigade in managing these conflicts. The research employs an empirical juridical approach. The results of this study are as follows: (1) The role of the Mobile Brigade in addressing social conflicts between Rarampadende Village and Pesaku Village is carried out in several stages, including a prevention stage, which emphasizes preventive measures, and a rehabilitation stage, which focuses on post-conflict recovery between the two villages. (2) The obstacles encountered by the Mobile Brigade include the low level of legal awareness among community members in the two villages and the limited number of mediators available to handle social conflicts. These factors hinder the Mobile Brigade’s effectiveness in resolving conflicts. The study provides the following recommendations: (1) All elements of society should cooperate in post-conflict recovery efforts, as addressing social conflicts is not solely the responsibility of the police but a shared responsibility of the entire community. (2) The local government of Sigi Regency should reactivate existing customary institutions, as conflict resolution using customary approaches—such as peace agreements and customary sanctions for violators—has proven to be effective in managing social disputes.